Carrier‐based PWM control strategy for three‐level indirect matrix converter. Issue 8 (28th June 2019) - Wang, Rutian; Zhong, Zhefu; Zhang, Jiawei; Wang, Weiquan
Abstract : This article proposes a new carrier‐based pulse width modulation (CBPWM) strategy for the control of TLIMC. The duty ratios of the rectifier stage and inverter stage are calculated by the SVPWM method. A carrier is constructed and combined with duty ratios to obtain modulation waves, which are regular and determined by the input voltage and output reference voltage. Then, the modulation waves are compared with the same carrier to obtain pulse signals. The pulse signals are used to produce driving signals of power switches through logic operation. The rectifier stage and inverter stage are controlled by the driving signals to obtain three‐phase symmetrical sinusoidal input and output waveforms. The proposed method is identical in output to the original SVPWM method. Finally, simulation and experimental results are provided to verify the feasibility and validity of the proposed method.